2018
DOI: 10.1016/j.reth.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Insulin secretion of mixed insulinoma aggregates-gelatin hydrogel microspheres after subcutaneous transplantation

Abstract: IntroductionThe objective of this study is to evaluate the insulin secretion of mixed aggregates of insulinoma cells (INS-1) and gelatin hydrogel microspheres after their subcutaneous transplantation.MethodsGelatin hydrogel microspheres were prepared by the conventional w/o emulsion method. Cell aggregates mixed with or without the hydrogel microspheres were encapsulated into a pouched-device of polytetrafluoroethylene membrane. An agarose hydrogel or MedGel™ incorporating basic fibroblast growth factor (bFGF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In addition, to increase the response speed of smart hydrogels to environmental stimuli and to enlarge their scope for application, hydrogels are usually prepared in the form of microspheres . There are many methods for preparing hydrogel microspheres (HMP), including emulsion crosslinking , micromolding‐based techniques , suspension polymerization , and microfluidic methods . However, some of these methods involve complex preparation processes, and they usually require the addition of other materials, such as stabilizing agents or surfactants, which are difficult to remove and may be potentially harmful impurities in biomaterials .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, to increase the response speed of smart hydrogels to environmental stimuli and to enlarge their scope for application, hydrogels are usually prepared in the form of microspheres . There are many methods for preparing hydrogel microspheres (HMP), including emulsion crosslinking , micromolding‐based techniques , suspension polymerization , and microfluidic methods . However, some of these methods involve complex preparation processes, and they usually require the addition of other materials, such as stabilizing agents or surfactants, which are difficult to remove and may be potentially harmful impurities in biomaterials .…”
Section: Introductionmentioning
confidence: 99%
“…However, the secreted insulin amount was less after transplantation and it was similar between 3 and 7 days after transplantation by in vivo studies [83].…”
Section: Gelatinmentioning
confidence: 82%
“…Hybrids of spacer materials between the cells can provide space and prevent such necrosis. Actually, hybrid cell spheroids that combine cells with functional material scaffolds have been studied. It has been reported that hybrid cell spheroids using calcium phosphate microparticles as spacers promote bone differentiation . Hybrid cell spheroids consisting of the hydrogel of alginate or gelatin and cells have been reported to improve cell viability and proliferation rate.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, hybrid cell spheroids that combine cells with functional material scaffolds have been studied. It has been reported that hybrid cell spheroids using calcium phosphate microparticles as spacers promote bone differentiation . Hybrid cell spheroids consisting of the hydrogel of alginate or gelatin and cells have been reported to improve cell viability and proliferation rate. It is thought that using these hydrogels, which are biocompatible and have high water content as spacers, enables cells to perform their original functions.…”
Section: Introductionmentioning
confidence: 99%